Oozing Matters: Infracycles of "Waste Management" and Emergent Naturecultures in Phnom Penh. Issue 2 (3rd April 2021) - Eitel, Kathrin
Abstract: The Cambodian city of Phnom Penh displays a unique recyclable waste collection system. This article follows the daily practices of waste pickers and the movements of recyclable waste through the city. The hereby examined recurrent daily interactions define the overall infrastructure of recyclable waste handling that can be described as infracycles : sociomaterial constellations through which the quotidian flows of persons, goods, tools, narratives and ideas are organized in a recurrent and circular manner, thereby functioning as an actual lived infrastructure. This infrastructure is lived out bottom-up, as waste pickers, depot owners, and others interrelate. As waste circulates through cycles, different sociomaterialities emerge, which shape the city. Keeping the city somewhat clean, waste pickers form material itineraries and direct flows that shape urban ecologies. In the same process, oozy materials leaking from infracycles also create new versions of the city in the form of urban naturecultures, which compete with other imaginaries and designs for Phnom Penh's urban transformation.